2020
DOI: 10.1002/app.50212
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic polyvinylpyrrolidone/chitosan/Fe3O4 electrospun nanofibers as effective U(VI) adsorbents

Abstract: Magnetoactive electrospun fibrous membranes consisting of polyvinylpyrrolidone (PVP), chitosan (CS) and pre‐fabricated, double‐layer oleic acid‐coated magnetite nanoparticles (OA.OA.Fe3O4) were fabricated and evaluated as new adsorbent materials for the removal and recovery of uranium (U(VI)) from aqueous solutions. The adsorption has been investigated by batch‐type experiments and the solid material has been characterized by X‐ray diffraction spectroscopy (XRD), Fourier‐transform infrared spectroscopy (FTIR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 76 publications
(79 reference statements)
2
3
0
Order By: Relevance
“…This result is in line with our group’s previous studies dealing with magnetically functionalized electrospun fibrous membranes that were evaluated as adsorbents for the removal of U(VI) and Eu(III) from aqueous solutions, [ 28 , 29 ] thus highlighting the significance of magnetic functionalization in the development of effective adsorbents destined for use in water-remediation processes.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This result is in line with our group’s previous studies dealing with magnetically functionalized electrospun fibrous membranes that were evaluated as adsorbents for the removal of U(VI) and Eu(III) from aqueous solutions, [ 28 , 29 ] thus highlighting the significance of magnetic functionalization in the development of effective adsorbents destined for use in water-remediation processes.…”
Section: Resultssupporting
confidence: 90%
“…More precisely, a 13% and 9% OFL removal was observed in the case of the pristine fibrous membrane at pH 4 and 6, respectively, whereas the percentage removal was increased to 39% and 21% when the magnetically functionalized fibrous adsorbent was used instead. The same positive effect of magnetic nanoparticle functionalization on the adsorption efficacy of previously reported electrospun fibrous membranes employed as substrates for the removal of various contaminants, including antibiotics from aqueous media, was also observed [ 28 , 29 , 60 ]. Exemplarily, Liu et al demonstrated the tetracycline removal from aqueous media at a pH range of 4–6, employing a Fe 3 O 4 -functionalized polyacrylonitrile electrospun membrane [ 60 ].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Intensive investigations performed recently led to the discovery of exceptional adsorbing substrates distinguished for both their specificity and effectiveness. The field extends from purely inorganic compounds such as carbon allotropes [11], metal oxides, and minerals [12] to organic-inorganic hybrids [11,13,14], composites [15,16], metal-organic frameworks (MOFs) [17][18][19], and aerogels [20][21][22]. Organic counterparts include conventional polymers [23,24], biopolymers [25,26], and dendritic polymers [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In one such example, we have developed magnetically functionalized fibrous adsorbents via electrospinning, consisting of random copolymers of the type poly(methyl methacrylate)-random-poly(2-(acetoacetoxy)-ethyl-methacrylate) (PMMA-co-PAEMA) bearing β-ketoester metal ion binding moieties, combined with poly(ethylene oxide) (PEO) and preformed oleic acid-coated magnetite nanoparticles that were successfully employed in the recovery of Eu(III). 22 In other studies of our group, pristine and magnetically functionalized polyvinylpyrrolidone (PVP)/ chitosan blended nanofibers have been successfully used as sorbents for U(VI) ions, 23,24 while the introduction of magnetic nanoparticles onto the fibers' surfaces resulted in an enhancement in the adsorption capacity of the nanocomposite fibrous adsorbents compared to that of the pristine fibrous analogues, reaching 183 mg/g. Thiourea-grafted electrospun polyacrylonitrile (PAN) fibers have been used for efficient Au(III) recovery from aqueous media.…”
Section: Introductionmentioning
confidence: 99%